DEVELOPMENT OF REGIONAL PLANNING BASED ON NORMALIZATION OF SEWERAGE CHANNELS IN STABAT DISTRICT, LANGKAT REGENCY - Dedek Syahputra Ginting; Abdi Sugiarto; Cut Nuraini (PT. Radja Intercontinental Publishing, 2025)
This study aims to develop regional planning based on drainage channel normalization in Stabat District, Langkat Regency, with a holistic and participatory approach. This area faces problems of flooding and waterlogging caused by drainage channels that are not functioning properly and are not integrated with existing spatial planning policies. This study identifies the existing condition of drainage channels, factors causing flooding and waterlogging, and the concept of developing regional planning that can integrate drainage channel normalization with spatial planning policies and environmental sustainability. The results of the study indicate that proper drainage channel normalization must involve all parties, including the government, community, and private sector, by considering technical, social, and environmental factors. This study recommends that drainage channel normalization be implemented with an integrated approach that involves active community participation, the use of environmentally friendly technology, and collaboration between related agencies. It is hoped that through the implementation of this strategy, the problems of flooding and waterlogging can be overcome, and the Stabat District area can develop sustainably.